In-situ carbon encapsulation of LiNi1/3Co1/3Mn1/3O2 using pillared ethylene glycol trapped in the metal hydroxide interlayers for enhanced cyclic stability. (10th October 2017) - Vasu, S.; Sahana, Moodakare B.; Sudakar, Chandran; Gopalan, R.; Sundararajan, G.
Graphical abstract: Highlights: Uniform C encapsulation on LNMCO under air ambient by an in-situ pyrolysis. Structurally trapped ethylene glycol in metal hydroxide layers as in-situ C source. Improved cyclic stability with a capacity retention of 82% (75%) after 150 (300) cycles. Enhanced shelf life of C-encapsulated LNMCO. Abstract: Carbon encapsulation of electrode materials is way to improve lifetime of lithium ion batteries by minimizing direct contact with electrolyte. However achieving uniform carbon encapsulation on electrochemically active metal oxides, specifically on layered compounds, is an extremely challenging task because of the contrastive-ambient requirement for the formation of carbon coating and the oxide. We demonstrate a novel in-situ method for uniform encapsulation of carbon on LiNi1/3 Mn1/3 Co1/3 O2 (LNMCO) using ethylene glycol (EG), which is intercalated in metal hydroxide interlayers pillaring the structure. Heat treating EG-pillared Ni1/3 Co1/3 Mn1/3 (OH)2 with lithium hydroxide under air ambient results in an uniform carbon coating during the growth and crystallization of LiNi1/3 Mn1/3 Co1/3 O2 particles. The trapping of carbon precursors in between the collapsed hydroxide layers minimizes the reaction of carbon precursor with oxygen even when heat-treated in air. This in-situ carbon encapsulation mechanism is revealed using detailed analyses carried out by Raman spectroscopy, TEM, EDS mapping and thermal analysis coupled with mass spectroscopy. Superior cyclic stability of C-LiNi1/3 Mn1/3 Co1/3 O2 with a capacity retention of 82% (75%) after 150 (300) cycles of charging/discharging is demonstrated with an optimum carbon thickness in contrast to 42% capacity retention in uncoated LNMCO samples after 100 cycles.